Gotowość szkolna dzieci sześcioletnich ze specjalnymi potrzebami edukacyjnymi uczniów pierwszej klasy szkoły podstawowej - Buchnat, Marzena (Wydawnictwo Naukowe UAM, 2013)
The child’s transition from pre-school to primary school is an important turning point in its development. In the light of changes related to the reduction of school-starting age and to the training system of students with special educational needs, matters of school maturity raise a lot of emotions and concerns in the context of school threshold age. Starting school education at the age of six, especially in the perspective of children with special educational needs, requires defi ning what school maturity is and how it should be analyzed in regard with the development possibilities of a child of this age. The research was to determine the level of school maturity of a six-year-old with special educational needs attending the fi rst class and to identify the areas of support of crossing that threshold so that these children could achieve success.
School Readiness for First Class of Sixyear-old Children with Special Educational Needs
Keywords: school readiness; student with special educational needs; six-year-old; school